Caracterización microestructural y de propiedades mecánicas en aceros de alta resistencia obtenidos por laminación en caliente y con tratamiento térmico de revenido - Chávez Cabrera, Wileduar David (2016)
In this research the mechanical and microstructural characteristics of an experimental high-strength steel obtained by hot rolling, were studied, both in the raw state of controlled rolling and after tempering heat treatment at subcritical temperatures of 400° C, 500° C and 620° C. Hardness measurements and microstructural analysis in longitudinal and transverse to the rolling direction were made. The results showed a marked anisotropy with respect to hardness. Regarding the microstructure it was determined that the smaller grain size occurs at 620 ° C, corresponding with a higher hardness. Small amounts of martensite and bainite presents distributed irregularly shaped homogenized with heat treatments.